Penerjemahan Ungkapan Idiom dalam Lirik Lagu Album ‘21’ Adele oleh Tribunnews - Amir, Afdila (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
The translation of idioms is one of the most challenging aspects of translation, as their meanings often differ from the literal interpretation of their components. This study analyses the translation of idioms in Adele's album 21 as translated by Tribunnews, focusing on the strategies employed using Mona Baker's (2011) translation theory. A total of 26 idioms were identified and examined to determine the methods used to adapt them into Indonesian. The results show that paraphrasing was the most frequently used strategy, applied to 13 idioms, followed by other strategies such as omission and using an idiom with similar meaning and form. The frequent use of paraphrasing indicates an effort to retain the meaning and emotional impact of the text while ensuring cultural relevance for the target audience. This research highlights the complexities of idiom translation in artistic works and contributes to a deeper understanding of idiom translation strategies in the media.